2018
DOI: 10.3390/jcm7020033
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Oncologic Outcomes, Opioid Use, and Complications after Esophageal Cancer Surgery

Abstract: Effective and adequate opioid use and prevention of postoperative complications are important for enhanced recovery after surgery. We examined the effects of postoperative opioid use and postoperative complications on overall survival and recurrence-free survival after esophageal cancer surgery. This retrospective cohort study analyzed the records of patients diagnosed with esophageal cancer who underwent the Ivor Lewis operation between January 2005 and December 2011. We collected data on total opioid use for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Single nucleotide polymorphism A118G have been previously linked with a reduced sensibility to exogenous opioids [27] and decreased cancer specific mortality probably due to the decreased immunosuppression associated with the G allele. Studies in breast and esophageal cancer patients found that the GG and GA alleles provided significant survival benefit compared to the AA allele [28][29][30]; it was hypothesized that a G allele increased sensitivity to endogenous opioid peptides [31,32]. In our study, we did not assess genetic polymorphism, and this could have contributed to our results, although any allele-specific in colorectal cancer patients remains to be elucidated.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Single nucleotide polymorphism A118G have been previously linked with a reduced sensibility to exogenous opioids [27] and decreased cancer specific mortality probably due to the decreased immunosuppression associated with the G allele. Studies in breast and esophageal cancer patients found that the GG and GA alleles provided significant survival benefit compared to the AA allele [28][29][30]; it was hypothesized that a G allele increased sensitivity to endogenous opioid peptides [31,32]. In our study, we did not assess genetic polymorphism, and this could have contributed to our results, although any allele-specific in colorectal cancer patients remains to be elucidated.…”
Section: Discussionmentioning
confidence: 81%
“…In previous studies equivalent morphine consumption has contradictory impact upon disease free survival. While it decreased survival on early stages of lung cancer [38] had no impact on colorectal or esophageal cancers [30,39,40].…”
Section: Discussionmentioning
confidence: 97%
“…However, we reported recently that remifentanil dosage during surgery was not clinically associated with OS or RFS in esophageal cancer surgery. 18 In summary, issues regarding the impact of epidural analgesia or opioid use on OS or RFS in lung cancer are still questionable. Therefore, the results of a prospective ongoing clinical trial (NCT01179308) will be important in the future.…”
Section: Discussionmentioning
confidence: 99%
“…There are two main pathological types of EC: esophageal squamous cell carcinoma (ESCC) and esophageal adenocarcinoma (EAC). ESCC is the most common histological type in developing countries, such as China [4,5]. The main treatments for EC are surgical resection, radiotherapy, and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%